2005
DOI: 10.1111/j.1365-2893.2005.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus carriers with persistently normal ALT levels: biological peculiarities and update of the natural history of liver disease at 10 years

Abstract: Some chronic hepatitis C (CHC) patients exhibit persistently normal alanine aminotransferase (ALT) levels (PNAL). Patients with PNAL experience significantly milder disease. In order to understand the differences between CHC patients with elevated ALT levels compared with those with PNAL better, we compared epidemiological, immunological and histological findings, in particular, the value of proliferating hepatocyte activity (PCNA) between the two groups of patients. We studied 40 chronic hepatitis C virus (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 29 publications
1
42
0
1
Order By: Relevance
“…CHC patients with persistently normal ALT serum levels show milder disease activity and lower hepatic proliferative activity index (29,30). Analyses of the patients with CHC and persistently normal serum ALT activity for miR-122 serum levels revealed that the miR-122 concentration in these patients were undistinguishable from those in healthy controls.…”
Section: Discussionmentioning
confidence: 97%
“…CHC patients with persistently normal ALT serum levels show milder disease activity and lower hepatic proliferative activity index (29,30). Analyses of the patients with CHC and persistently normal serum ALT activity for miR-122 serum levels revealed that the miR-122 concentration in these patients were undistinguishable from those in healthy controls.…”
Section: Discussionmentioning
confidence: 97%
“…HCV carriers with persistently normal ALT (PNALT) are more often females than chronic hepatitis C patients with abnormal ALT [40]. This distinction is likely due to lifestyle differences such as alcohol consumption [40], hormonal factors [41] or lower serum iron levels [42]. Although the normal range of ALT in HD patients with HCV may be different compared to the range in HCV carriers with normal renal function, our study demonstrated that females are more likely to have lower ALT levels, even in HD patients (Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…In a study of 24 patients with PNALT who underwent serial liver biopsies over a ten-year follow-up period, fibrosis stage remained stable 5 . In aggregate, these data support the favorable natural history of HCV with PNALT, but the potential still exists for progression to advanced liver disease.…”
Section: Natural History Of Chronic Hepatitis C With Persistently Normentioning
confidence: 99%